Clinical and Immunological Metrics During Pediatric Rhesus Macaque Development - Merino, Kristen M.; Slisarenko, Nadia; Taylor, Joshua M.; Falkenstein, Kathrine P.; Gilbert, Margaret H.; Bohm, Rudolf P.; Blanchard, James L.; Ardeshir, Amir; Didier, Elizabeth S.; Kim, Woong-Ki; Kuroda, Marcelo J. (Frontiers in Pediatrics, 2020)
Background: Clinical measurements commonly used to evaluate overall health of laboratory animals including complete blood count, serum chemistry, weight, and immunophenotyping, differ with respect to age, development, and environment. This report provides comprehensive clinical and immunological reference ranges for pediatric rhesus macaques over the first year of life. Methods: We collected and analyzed blood samples from 151 healthy rhesus macaques, aged 0-55 weeks, and compared mother-reared infants to two categories of nursery-reared infants; those on an active research protocol and those under derivation for the expanded specific-pathogen-free breeding colony. Hematology was performed on EDTA-anticoagulated blood using a Sysmex XT2000i, and serum clinical chemistry was performed using the Beckman AU480 chemistry analyzer. Immunophenotyping of whole blood was performed with immunofluorescence staining and subsequent flow cytometric analysis on a BD LSRFortessa. Plasma cytokine analysis was performed using a Millipore multiplex Luminex assay. Results: For hematological and chemistry measurements, pediatric reference ranges deviate largely from adults. Comparison of mother-reared and nursery-reared animals revealed that large differences depend on rearing conditions and diet. Significant differences found between two nursery-reared cohorts (research and colony animals) indicate large influences of experimental factors and anesthetic events on these parameters. Immune cells and cytokine responses presented with distinct patterns for infants depending on age, birth location, and rearing conditions. Conclusions: Our results illustrate how the immune system changed over time and that there was variability among pediatric age groups. Reference ranges of results reported here will support interpretations for how infection and treatment may skew common immune correlates used for assessment of pathology or protection in research studies as well as help veterinarians in the clinical care of infant nonhuman primates. We highlighted the importance of using age-specific reference comparisons for pediatric studies and reiterated the utility of rhesus macaques as a model for human studies. Given the rapid transformation that occurs in multiple tissue compartments after birth and cumulative exposures to antigens as individuals grow, a better understanding of immunological development and how this relates to timing of infection or vaccination will support optimal experimental designs for developing vaccines and treatment interventions.